Histopathology of Left Ventricular Mice Presented with Electrical Cigarettes (ENDS) and Conventional - Yanuarita Tursinawati Tursinawati; Noor Yazid Yazid; Findi Wira Purnawati (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2017)
ABSTRACTElectric Cigarette (ENDS) and conventional contains carbon monoxide (CO) which is a major cause of cardiovascular disease. CO is a dangerous substance since as free radicals it have high affinity for hemoglobin. Thus affinity could lead to tissue hypoxia resulting in cell death (necrosis) started by the cell nucleus pyknosis. In order to further study about the effect, this experiment is conducted to identify the histopathological appearence  of the left ventricle rat against exposure to electric cigarette (ENDS) and conventional. This study was conducted with a post test only control group design method. Samples contained 18 Rattus novergicus rat which was divided in 3 groups: control group (K) as a negative control,  P1 group were exposed by conventional cigarretes, and P2 group were exposed by ENDS. The treatment had been maintained for 30 days, followed by termination to perform the heart organ dissection and HE staining in order to made preparat. Preparat was observed by 400x lens of microscope to identify the pyknosis of the nuclei in 5 field of view. Data were analyzed with oneway ANOVA test with p<0,05 and  CI=95%. This study proved that there was a significant differences of pycnotic nuclei amount among the group (p-value=0,008). There was significant difference between group K with P1 (p=0,004), group K with group P2 (p=0,012). There was no significant difference between group P1 and P2 (p=0,567).It can be conluded that exposure to either electric cigarette (ENDS) or conventional cigarette gives significant effect to cell nucleus pycnosis. Meanwhile, the effect comes from exposure of electric cigarette smoke (ENDS) has no significant difference with conventional cigarette. Keywords:  histopathological appearance of  left ventricle, electrical cigarette, ENDS, conventional cigarette ABSTRAKRokok elektrik (ENDS) dan konvensional mengandung karbonmonoksida (CO) yang diduga berperan utama menyebabkan penyakit kardiovaskuler.CO merupakan zat yang berbahaya karena sebagai radikal bebas dan sifatnya yang memiliki afinitas yang tinggi terhadap Hemoglobin. Hal ini dapat menyebabkan hipoksia jaringan yang mengakibatkan kematian sel (nekrosis) ditandai dengan inti sel yang piknosis. Tujuan penelitian ini untuk mengidentifikasi gambaran histopatologi ventrikel kiri tikus terhadap paparan rokok elektrik (ENDS) dan konvensional. Penelitian ini merupakan penelitian eksperimental dengan rancangan post test only control group design. Sampel adalah tikus Rattus norvegicus dengan jumlah 18 ekor dibagi dalam 3 kelompok, yakni kelompok K sebagai kontrol negatif, kelompok P1 diberikan paparan Rokok Konvensional dan kelompok P2 diberikan paparan rokok elektrik (ENDS). Sampel diperlakukan selama 30 hari, kemudian diterminasi untuk pengambilan organ jantung dan dibuat preparat dengan pengecatan HE. Pembacaan preparat dengan mikroskop perbesaran 400x untuk melihat inti sel piknotik pada 5 lapang pandang. Data dianalisis menggunakan uji Oneway ANOVA dengan p<0,05 dan CI=95%. Dari hasil penelitian didapatkan perbedaan yang bermakna jumlah inti sel piknotik pada ketiga kelompok (p-value=0,008). Terdapat perbedaan yang signifikan antara kelompok K dan P1 (p=0,004), kelompok K dan P2 (p=0,012). Namun antar kelompok P1 dan P2 tidak terdapat perbedaan bermakna (p=0,567).Paparan rokok elektrik dan konvensional memiliki efek yang signifikan dibanding kontrol terhadap jumlah inti piknotik. Namun, Jumlah inti sel piknotik ventrikel kiri tikus tidak mengalami perbedaan bermakna antara paparan asap rokok elektrik (ENDS) dan konvensional. Kata kunci: Histopatologi ventrikel kiri, rokok elektrik,ENDS, rokok konvensional.